IMPLEMENTASI KURIKULUM BINA PRIBADI ISLAMI (BPI) DALAM PEMBENTUKAN AKHLAKUL KARIMAH DI SDIT ULUL ALBAAB WELERI KENDAL - Sunarso; Rahmat Setiawan (As-Sulthan Journal of Education, 2025)
The Bina Pribadi Islami (BPI) curriculum plays a key role in shaping students' moral character (akhlaqul karimah) at SDIT Ulul Albaab Weleri, Kendal. This study explores the strategies, processes, and impacts of the BPI curriculum in fostering Islamic values and noble character. Using qualitative methods, data were gathered through interviews, observations, and documentation. The results show effective integration of the BPI curriculum in daily activities, extracurricular programs, and school culture. Religious practices like tahfidzul Qur'an, dhuha prayers, and moral guidance significantly influence students' behavior, instilling Islamic values as the basis of character development.